2006
DOI: 10.3354/meps323107
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of coral recruitment by macroalgae and cyanobacteria

Abstract: Coral recruitment is a key process in the maintenance and recovery of coral reef ecosystems. While intense competition between coral and algae is often assumed on reefs that have undergone phase shifts from coral to algal dominance, data examining the competitive interactions involved, particularly during the larval and immediate post-settlement stage, are scarce. Using a series of field and outdoor seawater table experiments, we tested the hypothesis that common species of macroalgae and cyanobacteria inhibit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
332
5
5

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 393 publications
(353 citation statements)
references
References 45 publications
11
332
5
5
Order By: Relevance
“…Many species of coral larvae require CCA to settle (Morse et al 1988;Heyward and Negri 1999), and availability of CCA is negatively correlated with macroalgal abundance (Hixon 1997). Dictyota spp., the most abundant fleshy algae observed in this study, was not as abundant on these patch reefs (15.4 ± 0.8% cover) compared to other locations on the Florida reef tract (Lirman and Biber 2000;Beach et al 2003;Kuffner et al 2006), whereas SSS was fairly abundant (overall mean 21% cover). In a study conducted in this area in 1981, Burns (1985) reported that they observed lots of "uncolonized reef substrate."…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…Many species of coral larvae require CCA to settle (Morse et al 1988;Heyward and Negri 1999), and availability of CCA is negatively correlated with macroalgal abundance (Hixon 1997). Dictyota spp., the most abundant fleshy algae observed in this study, was not as abundant on these patch reefs (15.4 ± 0.8% cover) compared to other locations on the Florida reef tract (Lirman and Biber 2000;Beach et al 2003;Kuffner et al 2006), whereas SSS was fairly abundant (overall mean 21% cover). In a study conducted in this area in 1981, Burns (1985) reported that they observed lots of "uncolonized reef substrate."…”
Section: Discussioncontrasting
confidence: 76%
“…A mean of 20.8 ± 1.1% of the bottom was assigned to the category SSS, defined as hard substratum covered mostly in crustose coralline algae (CCA) and lacking sediments >1 mm deep, macroalgae, or thick turf algae as previously described in Kuffner et al (2006). This category was considered to be an index of suitable settlement substratum for coral larvae and is analogous to the "cropped substratum" category of .…”
Section: Benthic Variablesmentioning
confidence: 99%
“…A study of the recruitment of coral larvae in Guam found that the presence of L. majuscula significantly reduced larval survival in Acropora surculosa and recruitment in Pocillopora damicornis (Kuffner and Paul, 2004). Similar studies in the Florida Keys showed that larvae of Porites astreoides avoided settling near Lyngbya polychroa and Lyngbya confervoides on recruitment tiles and that L. majuscula negatively impacted survival and recruitment of larvae of the octocoral Briareum asbestinum (Kuffner et al, 2006). These studies highlight the potential for secondary metabolites to influence the structure of marine ecosystems, and demonstrate the lack of knowledge surrounding the allelopathic role of LTA and other cyanobacterial secondary metabolites.…”
Section: Lyngbyatoxin Amentioning
confidence: 57%
“…have been isolated from algal biofilms and coral mucus (de Castro et al, 2010;Horta et al, 2014), and there is some evidence linking Staphylococcus strains to coral disease (Kellogg et al, 2013). Cyanobacteria, especially those in the order Oscillatoriales, inhibit settlement of coral larvae and have been implicated as causative agents of black band disease (Frias-Lopez et al, 2003;Kuffner and Paul, 2004;Kuffner et al, 2006;Casamatta et al, 2012). Larvae of multiple coral species avoid settling on the surface of P. solubile Ritson-Williams et al, 2014), and this may be due to inhibitory microbial OTUs that cause larval avoidance of this species of CCA.…”
Section: Interspecies Variability: Compositionmentioning
confidence: 99%